2015
DOI: 10.1242/jeb.123794
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among plumage coloration, blood selenium concentrations, and immune responses of adult and nestling tree swallows

Abstract: In a number of taxa, males and females both display ornaments that may be associated with individual quality and could be reliable signals to potential mates or rivals. We examined the iridescent blue/green back and white breast of adult tree swallows (Tachycineta bicolor) to determine whether plumage reflectance is related to adult or offspring immune responses. We simultaneously addressed the influence of blood selenium levels and the interaction between blood selenium and plumage coloration on adult and nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 82 publications
0
17
1
Order By: Relevance
“…Previous studies showed that bluer plumage ornaments are condition-dependent in juveniles (Johnsen et al, 2003;Jacot & Kempenaers, 2007;Peters et al, 2007 in blue tits, Siefferman, Shawkey, Bowman, & Woolfenden, 2008;Siefferman & Hill, 2007 in other species) and in adults (Beck, Hopkins, & Hawley, 2015;Doutrelant, Grégoire, Midamegbe, Lambrechts, & Perret, 2012;Galván, 2011), which contrasts with the negative genetic association that we found between hue, UV chroma and performance traits.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies showed that bluer plumage ornaments are condition-dependent in juveniles (Johnsen et al, 2003;Jacot & Kempenaers, 2007;Peters et al, 2007 in blue tits, Siefferman, Shawkey, Bowman, & Woolfenden, 2008;Siefferman & Hill, 2007 in other species) and in adults (Beck, Hopkins, & Hawley, 2015;Doutrelant, Grégoire, Midamegbe, Lambrechts, & Perret, 2012;Galván, 2011), which contrasts with the negative genetic association that we found between hue, UV chroma and performance traits.…”
Section: Discussioncontrasting
confidence: 99%
“…By waiting to escalate, these females may avoid energetically costly aggressive interactions and reduce their risk of injury. Female tree swallows that are more aggressive or have experimentally elevated testosterone produce lower quality offspring (Rosvall 2008(Rosvall , 2013 and we previously found brighter white females have young with a stronger innate immune response (Beck et al 2015a). It is possible that there is a trade-off between aggression and investment in offspring or self-maintenance that is related to white brightness.…”
Section: Discussionmentioning
confidence: 91%
“…It is possible that male tree swallows adjust their nest box defense in response to the ornamentation of their mates. Females with brighter white breasts have offspring with stronger bactericidal capacity which suggests that these females are of higher quality or invest more in reproduction, making them potentially valuable mates (Beck et al 2015a). Males paired to brighter white females could be more likely to defend the nest box against an intruding female and greater nest defense by the male could lead brighter white females to respond less strongly to an intruding female.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While second-year (SY) females possess dull grey plumage, males and ASY 96 females bear iridescent upperparts which range in colour from green to blue among individuals 97 (Hussell, 1983a). Delayed plumage maturation has been demonstrated to reduce conspecific 98 aggression towards SY females during territorial intrusions, an adaptive trait in a species for 99 which nest site competition is very high (Coady and Dawson, 2013 (Beck et al, 2015) compared to greener males. In females, bluer feathers are associated with 106 older females and greater fledging success , and plumage brightness is 107 positively correlated with total clutch egg mass .…”
mentioning
confidence: 99%